An Introduction to the Late Pleistocene Lithic Industries in the East of the Iranian Plateau in Light of the New Findings from Sarbisheh Plain. - Sadraei, Ali; Farjami, Mohammad; Zafaranlou, Roghayeh; Vahedi, Hossein (Lithic Technology, 2022)
In the present study, in the first step, we introduce and study the newly-discovered site of Kalateh Mohammad Laleh in Sarbisheh plain and then by combining this collection and the lithic artifacts of the other four sites, namely Kiaram, Khunik, Kalateh Shour and Chehel Dokhtaran, we investigate the main characteristics of their lithic artifacts. Accordingly, in the two collections of Kiaram and Khunik, an industry similar to the Zagros Mousterian industry can be observed and in the other two collections of Kalateh Shour and Chehel Dokhtaran, the dominant Levallois Technique can be traced. Although our studies show a relative correlation between the Kalateh Mohammad Laleh collection and the two collections of Kiaram and Khunik, the sampling error of surface collections should not be ignored. This, along with the lack of stratigraphic evidence, poses serious challenges for achieving a clear picture of the lithic industries of east the Iranian plateau.